(untitled) (Research, Society and Development, 2021)
Objective: A descriptive analysis of the sociodemographic profile of patients diagnosed with major depressive disorder was performed; in addition to establishing a correlation on personal factors, somatic sensitivity parameters, physiological characteristics and use of pharmacological treatment in the group with MDD and healthy individuals. Methods: The database was analyzed from March to May 2019, referring to the evaluation sheets applied to employees and students of the Federal University of Pará, later the statistical evaluation was carried out using the Microsoft Office Excel® 2013 program and the Bioestat – version 5.3. Results: In the sociodemographic profile of the 50 participants evaluated, the majority were female 29 (58%), with a strong association between gender (p = 0.0219) with this mental disorder. Altered regular bowel function showed a 100% increase between GTDM and GC. Among the variables related to somatic sensations, the presence of pruritus was the variable with an important difference between the groups, with CG 23 (92%) without change in sensitivity to itching, compared to GTDM 11 (44%) patients reported the presence of pruritus. There was a statistically strong association between hair loss and sleep quality in the depressive disorder group. Conclusion: It is concluded that patients with major depressive disorder have risk factors specific to the individual and somatic symptoms that influence the course of disease resolution. Further studies are suggested to relate sociodemographic characteristics, presence of somatic symptoms and drug interactions to identify possible factors associated with major depression in the university population.